2006
DOI: 10.1542/peds.2005-1098
|View full text |Cite
|
Sign up to set email alerts
|

Lead Toxicity in a 14-Year-Old Female With Retained Bullet Fragments

Abstract: In the past 3 decades, lead levels in North American children have been declining. Despite the decline in lead exposure, lead toxicity remains a significant childhood environmental health hazard. The usual route of lead exposure is through ingestion, but lead toxicity secondary to retained bullet fragments has been well documented in the adult literature. The diagnosis of lead toxicity is often difficult and delayed secondary to vague and transient symptoms. Recognizing high-risk characteristics of bullet frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 10 publications
1
40
0
4
Order By: Relevance
“…Yapılan araştır-malarda, ateşli silah yaralanmasına bağlı vücutta kalan mermi çekirdeği ya da saçma tanesi artıklarının kan kurşun düzeyini artırdıkları ve buna bağlı uzun dö-nemli etkisi yanı sıra kısa dönemde kronik karın ağrısı, kusma ve anoreksiye neden olabileceği bildirilmiştir. [11][12][13] Olgumuzda, akut dönemde görüldüğü bildirilen semptomların gelişmediği, kan kurşun düzeyinin 3.40 µg/dL olduğu tespit edilmiştir.…”
Section: Discussionunclassified
“…Yapılan araştır-malarda, ateşli silah yaralanmasına bağlı vücutta kalan mermi çekirdeği ya da saçma tanesi artıklarının kan kurşun düzeyini artırdıkları ve buna bağlı uzun dö-nemli etkisi yanı sıra kısa dönemde kronik karın ağrısı, kusma ve anoreksiye neden olabileceği bildirilmiştir. [11][12][13] Olgumuzda, akut dönemde görüldüğü bildirilen semptomların gelişmediği, kan kurşun düzeyinin 3.40 µg/dL olduğu tespit edilmiştir.…”
Section: Discussionunclassified
“…In the synovium, lead can cause synovitis, joint deterioration, systemic absorption, and death, sometimes decades after the accident. The projectile location and its fragmentation with bone interface, in contact with the cerebrospinal fluid, synovial fluid, or pleural surface area, and duration of exposure are crucial for increased absorption and risk of toxicity 6 . In the body, bones are the main natural reservoir of lead.…”
Section: Discussionmentioning
confidence: 99%
“…But could the patient develop lead toxicity after such a long interval from the gunshot wound? It has been demonstrated that blood lead levels tend to increase with time after injury in patients with projectile retention 7 .Onset of symptoms from the initial gunshot wound has been reported from 2 days up to 52 years 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The usual route of lead exposure is oral ingestion, but toxicity secondary to retained bullet fragments has been well documented 1 . Switz et al described the first case in 1976 -a bullet was lodged in a patient's left ankle and gastrointestinal symptoms emerged forty years after the wound 2 .…”
mentioning
confidence: 99%